2008
DOI: 10.1371/journal.pone.0003942
|View full text |Cite
|
Sign up to set email alerts
|

Heterosubtypic Neutralizing Monoclonal Antibodies Cross-Protective against H5N1 and H1N1 Recovered from Human IgM+ Memory B Cells

Abstract: BackgroundThe hemagglutinin (HA) glycoprotein is the principal target of protective humoral immune responses to influenza virus infections but such antibody responses only provide efficient protection against a narrow spectrum of HA antigenic variants within a given virus subtype. Avian influenza viruses such as H5N1 are currently panzootic and pose a pandemic threat. These viruses are antigenically diverse and protective strategies need to cross protect against diverse viral clades. Furthermore, there are 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
774
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 696 publications
(803 citation statements)
references
References 46 publications
24
774
1
4
Order By: Relevance
“…Notably, the highest induction of ADCC in response to HA1 or the HA trimer was detected in the pre-pandemic samples (#3 and #51, Fig. 5 Several studies have shown pre-existing immunity against A(H1N1)2009 in adults (Corti et al, 2010(Corti et al, , 2011Ekiert et al, 2009;Throsby et al, 2008), whereas little or no preexisting cross-reactive antibodies were detected in a group of 124 children aged 6 months to 9 years (Hancock et al, 2009) the HA2 domain, which is not presented in our array (Greenbaum et al, 2009;Li et al, 2012).…”
Section: Adcc Induction Pre-and Post-a(h1n1)2009 Infectionmentioning
confidence: 73%
See 1 more Smart Citation
“…Notably, the highest induction of ADCC in response to HA1 or the HA trimer was detected in the pre-pandemic samples (#3 and #51, Fig. 5 Several studies have shown pre-existing immunity against A(H1N1)2009 in adults (Corti et al, 2010(Corti et al, , 2011Ekiert et al, 2009;Throsby et al, 2008), whereas little or no preexisting cross-reactive antibodies were detected in a group of 124 children aged 6 months to 9 years (Hancock et al, 2009) the HA2 domain, which is not presented in our array (Greenbaum et al, 2009;Li et al, 2012).…”
Section: Adcc Induction Pre-and Post-a(h1n1)2009 Infectionmentioning
confidence: 73%
“…Persons born before the 1940s were most protected against the A (H1N1)2009, which has been related to the similarity between the HA1 of the 1918 and 2009 pandemic strains Xu et al, 2010); however, some protection was also observed in younger adults. Cross-neutralizing antibodies have been implicated in this immune protection, possibly resulting from the boosting of antibodies that had developed against previous seasonal strains ( Corti et al, 2010Corti et al, , 2011Ekiert et al, 2009;Li et al, 2012;Throsby et al, 2008;Wrammert et al, 2011). However, cross-reactive antibodies were hardly detected among children aged 6 months to 9 years (Hancock et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, human IgM + memory B cells can produce neutralizing Abs against existing and extinct influenza virus species, thus providing efficient cross-protection (48). Notably, the major proportion of CD27 + memory B cells in human blood expresses IgM (49), and BCL-6 mutation analysis suggests that these cells are derived from a T cell-dependent GC reaction (50).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there exist highly conserved epitopes in the stem region of the HA molecule that may become a target for a "universal flu vaccine" (3,7,10,14,15). Humanized monoclonal antibodies raised against these conserved epitopes from a single influenza virus strain were shown to provide strong cross-protection against heterologous strains (13).…”
Section: Discussionmentioning
confidence: 99%